Types and Eruption Patterns of the Carboniferous Volcanic Edifices in the Shixi Area, Junggar Basin - Yiming, Abulimiti; Bian, Baoli; Liu, Longsong; Chen, Hailong; Shan, Xuanlong; Li, Ang; Yi, Jian (Frontiers in Earth Science, 2022)
The types of volcanic edifices and volcanic eruption patterns control the accumulation and distribution of oil and gas. By means of drilling, seismic and geochemical analysis, the types and distribution of Carboniferous volcanic edifices in the Shixi area of Junggar Basin were studied, and the formation mechanism of magma was clarified, and the eruption patterns of volcanoes were investigated. The results show that the types of Carboniferous volcanic edifices in the Shixi area mainly include stratovolcanic edifices, basic shield volcanic edifices and mounds superimposed volcanic edifices. Stratovolcanic edifices and mounds superimposed volcanic edifices are developed around Shixi fault, while single stratovolcanic edifices are developed around Mobei fault. Basic shield volcanic edifices are only developed in the south of Shixi area. Vertically, volcanic edifices are mainly developed on the hanging wall of the faults. When the faults develop, the volcanic vents are dendritic, forming mounds superimposed volcanic edifices in space. On the plane, there are more volcanic edifices in Shixi salient than mobei salient. Intermediate-acid volcanic edifices are distributed in beaded shape along one side of Shixi fault and Mobei fault, while basic volcanic edifices are distributed in sheet shape on both sides of Dinan fault. In the early Carboniferous, the Shixi area was in the island arc environment under the subduction of oceanic crust. The basic magma came from the melting of subduction plate, and the intermediate-acid magma came from the partial melting of the crust. In the late carboniferous, the extensional environment formed by the retraction of subduction plate led to the formation of large-scale volcanic eruption. The extensional environment formed by the retreat of subduction plate in the later stage resulted in a large scale volcanic eruption.